Unraveling the Implications of Globalization and Technology on the Political System in Global Challenges to Constitutional Law - Heru Riyadi (LEGAL BRIEF, 2024)
Globalization and technology have become two dominant forces that have significantly changed the political and constitutional legal landscape throughout the world. This research uses a qualitative approach and descriptive analysis to discuss the impact of globalization and technology on the political system in global challenges to constitutional law. This approach allows researchers to gain a deep understanding of the complexity of the interactions between the two phenomena, while descriptive analysis is used to describe the research findings in detail. Data was collected through literature studies and direct observation of political phenomena and constitutional law that occurred in various countries. The research results found that globalization and technology have significantly changed the political and constitutional legal landscape throughout the world. Globalization not only has an impact on economic aspects, but also includes interrelated political and cultural aspects. Advances in information and communications technology, such as the internet and social media, have accelerated political participation, increased government transparency, and influenced the function of constitutional law. To overcome these challenges, a deep understanding of constitutional principles, the rule of law, and public participation is essential. By understanding the implications of globalization and technology on the political system, it is hoped that effective strategies can be developed to maintain the integrity of constitutional law in facing the ever-growing dynamics of global change